Bacterial diversity and community structure along the glacier foreland of Midtre Lovénbreen, Svalbard, Arctic. (July 2021) - Venkatachalam, Siddarthan; Kannan, Vatharamattathil Mohanan; Saritha, Vadakke Neelamanakesavan; Loganathachetti, Dinesh Sanka; Mohan, Mahesh; Krishnan, Kottekkatu Padinchati
Highlights: Bacterial diversity was diverse along the glacier foreland of Midtre Lovénbreen. Alpha diversity indices varied based on deglaciation phase of the glacier foreland. Chemolithotrophic bacteria were abundant in the recently deglaciated region. pH, Cr, Cd and Ca influenced the bacterial community structure. Abstract: Polar regions provide an ideal environment to investigate the succession of bacterial communities. In the present study, we investigated the bacterial diversity and community structure of the Midtre Lovénbreen glacier foreland ecosystem using a chronosequence approach. The alpha diversity indices of the samples collected from recently deglaciated sites comprised of less diverse, yet abundant bacterial groups compared to the samples from comparatively older sites, where the bacterial diversity was very rich and evenly distributed. Bacterial phyla viz. (a) Proteobacteria (14–44.58%) comprising classes of alpha- and gamma Proteobacteria along with (b) Actinobacteriota (8.8–33.8%) were predominantly distributed across the samples, while phyla Bacteroidota (up to 21%) was mainly distributed in the recently deglaciated samples and phyla Acidobacteriota (up to 24%) in deglaciated samples which were older. Bacterial families (Sulfurovaceae and Sulfurimonadaceae) affiliated with bio weathering of rocks for their energy metabolism was also detected in the present study from the recently deglaciated region. Bacterial genera belonging to Luteolibacter (up to 10.25%), Polaribacter (up to 12.32%), Acidimicrobium (6%) and Sulfitobacter (13.6%) were highly abundant in the recently deglaciated samples, while Candidatus_Udaeobacter (up to 17%) and RB41 (up to 10.5%) were found to be abundant in the older stage samples. Linear discriminant analysis revealed 121 Operational Taxonomic Units that could be attributed to the differences in the community diversity between the two groups. Among the analyzed environmental variables, pH, Cr, Cd and Ca significantly contributed to the differences in the bacterial community structure.